IMPORTANCE OF AUTISM DETECTION DEVELOPMENT PROBLEMS OF TODDLER-AGE CHILDREN IN DENSELY POPULATED SETTLEMENTS - Permaida Permaida; Mey Lona Verawaty Zendrato; Komang Noviantari; Malianti Silalahi (JMM (Jurnal Masyarakat Mandiri), 2025)
Abstrak: Masalah perkembangan anak terutama autis sering kali diabaikan di wilayah pemukiman padat penduduk dikarenakan tingginya tuntutan pekerjaan dan hipitan ekonomi orang tua sehingga anak berisiko tinggi mengalami keterlambatan penanganan. Autisme merupakan kesulitan dalam interaksi sosial, perilaku dan komunikasi terutama non verbal. Tanda dan gejala muncul pada anak berusia sebelum 36 bulan. Kegiatan PKM ini bertujuan mengidentifikasi masalah perkembangan anak autism dipemukiman padat penduduk menggunakan modified checklist for autism in toddlers (M - CHAT). Metode PKM ini adalah praktik pemeriksaan perkembangan anak menggunakan alat deteksi modified checklist for autism in toddlers (M - CHAT) kepada 13 anak toodler yang dilaksanakan di tempat mitra kami Yayasan Rahmat Empati di Pondok Empati, Jakarta Barat. Hasil pemeriksaan alat deteksi modified checklist for autism in toddlers (M - CHAT) pada anak toodler sebesar 100% tidak ditemukan masalah autisme. Penggunaan Modified checklist for autism in toddlers (M - CHAT) menjadi alat skrining pencegahan autisme yang mudah digunakan dan dilakukan secara rutin oleh mitra karena telah ditetapkan oleh Kementerian Kesehatan Republik Indonesia. Pemeriksaan perkembangan sejak dini pada anak toodler sangat penting untuk mendukung kesejahteraan mereka.Abstract: Child development issues, especially autism, are often ignored in densely populated residential areas due to high work demands and the economic pressures of parents, so children are at high risk of experiencing delays in treatment. Autism is a difficulty in social interaction, behavior, and communication, especially non-verbal. Signs and symptoms appear in children under 36 months of age. This PKM activity aims to identify developmental problems of autism children in densely populated residential areas using the modified checklist for autism in toddlers (M - CHAT). This PKM method examines child development using the modified checklist for autism in toddlers (M - CHAT) detection tool for 13 toddlers, which was carried out at our partner Yayasan Rahmat Empati in Pondok Empati, West Jakarta. The results of the examination of the modified checklist for autism in toddlers (M - CHAT) detection tool in toddlers were 100% found to have no autism problems. A modified checklist for autism in toddlers (M - CHAT) is an easy-to-use autism prevention screening tool. It is carried out routinely by partners because it has been determined by the Ministry of Health of the Republic of Indonesia. Early developmental examinations in toddlers are very important to support their well-being.